PENGEMBANGAN E-LKPD BERBASIS HOTS (Higher Order Thingking Skills) PADA PEMBELAJARAN LINGKUNGAN PESISIR DI SMA NEGERI 2 TILAMUTA - Ramin Tanu, Wahyuni; Nusantari, Elya; Sidik Katili, Abubakar; Utina, Ramli; Mustaqimah, Nur (Jurnal Biogenerasi, 2025)
This study aims to develop an Electronic Student Worksheet (E-LKPD) based on Higher Order Thinking Skills (HOTS) using a Problem Based Learning (PBL) approach on coastal environment material at SMA Negeri 2 Tilamuta. The background of this study is the low level of student involvement and the limited availability of teaching materials that foster critical thinking and problem-solving abilities, especially regarding coastal ecosystem topics. The research applies the Research and Development (R&D) method, specifically using the ADDIE model at the development stage, which includes needs analysis, product design, and limited trials involving 26 grade X students and a Biology teacher. Data collection techniques included questionnaires, observations, and interviews, analyzed using both quantitative and qualitative approaches. The results revealed that the developed E-LKPD was highly practical, with teacher response reaching 96.9% and student response 94.5%. Observations also showed the implementation of teacher and student activities reached 100%, 100%, and 95% across three meetings. These findings indicate that the HOTS-based E-LKPD effectively encourages student engagement, enhances conceptual understanding, and creates a meaningful, enjoyable learning experience. Thus, the E-LKPD is suitable to be used as an adaptive, interactive, and contextual learning tool that meets the demands of 21st-century education, especially in enhancing students' critical thinking and problem-solving skills.